Which socio-demographic factors are associated with participation in oral cancer screening in the developing world? Results from a population-based screening project in India - Ramadas, K. (2008)
Background: This study examines socio-demographic determinants of participation in a population-based randomized controlled trial that proved that oral visual inspection was effective in reducing oral cancer mortality in high-risk individuals in India. Methods: Multivariate logistic regression was used to establish socio-demographic characteristics of participants versus non-participants in the intervention arm. Compliance with referral was analysed according to the socio-demographic characteristics of screen-positives. Results: Of 96,517 eligible subjects, 87,655 were screened, 8688 individuals never received the invitation and 174 refused screening. Compared to the non-screened, a higher proportion of screened individuals were women (OR=4.51; CI: 4.28–4.75), lived in better housing (OR=1.35; CI: 1.25–1.41), had television/radio (OR=1.50; CI: 1.43–1.58) and were tobacco and alcohol users (OR=2.75; CI: 2.57–2.95). Being 65 and older decreased the chances of screening (OR=0.39; CI: 0.37–0.42), as well as living in high-size households (OR=0.73; CI: 0.68–0.78). Sixty-three percent of 5143 screen-positives complied with referral. Controlling for all other factors, individuals older than 44, and those with more advanced lesions were more likely to comply with referral (p<0.001). Individuals living in better housing were less likely to comply with referral (OR=0.79; CI: 0.65–0.95). Conclusions: In summary, adequate coverage can be obtained in population-based oral screening in developing countries. The study underscores the important role of patient-provider communication in assuring high compliance with referral.